Module of selecting the company development strategic goals in the Enterprise Performance Management System - Moskalenko, V. (М. О. Бондаренко, 2018)
The procedure for the strategic goals setting has been considered as a part of the business process for creation of the enterprise development program. For goals selection it is proposed to use the Analytic Hierarchy Process. In consequence of application of direct and reverse analytic hierarchy process, are determined the estimates of changes in the enterprise performance when the goals are reached. Realizing the Analytic Hierarchy Process is carried the comparison of the estimates of changes in the company performance indicators when achieving the goals in question. By analyzing these estimates the potential goals and achievement strategies are selected. Strategies are defined by the aspects of the company development: production, finance, personnel, marketing. The result of this procedure is desired strategic goals selected from among all of such goals which would be less risky, i.e. would be to a lesser extent subject to external impacts. The business process of the development program forming is the basis of the strategic planning module of the Enterprise Performance Management system. Implementation of such a process will permit to realize the strategic alignment and to increase the company efficiency by setting adequate strategic goals.
Keywords: strategic alignment; strategic goal; development strategy; development program; analytic hierarchy process